AWS administration : the definitive guide : learn to design, build, and manage your infrastructure on the most popular of all cloud platforms--Amazon Web Services - Wadia, Yohan Rohinton (Professional experience distilled., 2016)
Learn to design, build, and manage your infrastructure on the most popular of all the Cloud platformsAmazon Web ServicesAbout This Book Learn how to leverage various Amazon Web Services (AWS) components and services to build a secure, reliable, and robust environment to host your applications on Deep dive into the core AWS service offerings with hands-on tutorials, real-world use case scenarios, and best practices A self-paced, systematic, and step-by-step guide to learning and implementing AWS in your own environmentWho This Book Is ForThis book is for those who want to learn and leverage AWS. Although no prior experience with AWS is required, it is recommended that you have some hands-on experience of Linux, Web Services, and basic networkingWhat You Will Learn A brief introduction to Cloud Computing and AWS accompanied by steps to sign up for your first AWS account Create and manage users, groups, and permissions using AWSS Identity and Access Management services Get started with deploying and accessing EC2 instances, working with EBS Volumes and Snapshots Customize and create your very own Amazon Machine Image Design and deploy your instances on a highly secured, network isolated environment using Amazon VPC Effectively monitor your AWS environment using specialized alarms, custom monitoring metrics, and much more Explore the various benefits of Database-as-a-Service offerings and leverage them using Amazon RDS and Amazon DynamoDB Take an in-depth look at what's new with AWS, including EC2 Container Service and Elastic File SystemIn DetailAWS is at the forefront of Cloud Computing today. Many businesses are moving away from traditional datacenters and toward AWS because of its reliability, vast service offerings, lower costs, and high rate of innovation. Because of its versatility and flexible design, AWS can be used to accomplish a variety of simple and complicated tasks such as hosting multitier websites, running large scale parallel processing, content delivery, petabyte storage and archival, and lots more. Whether you are a seasoned sysadmin or a rookie, this book will provide you with all the necessary skills to design, deploy, and manage your applications on the AWS cloud platform. The book guides you through the core AWS services such as IAM, EC2, VPC, RDS, and S3 using a simple real world application hosting example that you can relate to. Each chapter is designed to provide you with the most information possible about a particular AWS service coupled with easy to follow hands-on steps, best practices, tips, and recommendations. By the end of the book, you will be able to create a highly secure, fault tolerant, and scalable environment for your applications to run on. Style and approach This in-depth and insightful guide is filled with easy-to-follow examples, real-world use cases, best practices, and recommendations that will help you design and leverage AWS.